Labour makeup: a case study of 800, 000 cosmetics resellers in Brazil. (1st July 2011) - Ludmila Costhek Abilio,
Abstract : This article presents a case study a Brazilian company, Natura, which employs over 800, 000 women as cosmetics resellers who are responsible for all aspects of product distribution. The article discusses the status of informal workers and examines the definition of informal labour in its modern form. The relationship between informal labour and brand is analysed while taking into account the connection between labour and consumption in the resellers' activities. The analysis centres on the relationship between a typically female workforce, labour exploitation, and capital accumulation.